UPAYA MENANGGULANGI PKL GAGAL BAYAR DALAM PEMBIAYAAN MENGGUNAKAN AKAD RAHN DI BMT NUT (PERSPEKTIF BASYARNAS) - Afifatul Bariroh; Kholis Firmansyah (Universitas KH. A. Wahab Hasbullah, 2020)
Many BMT are experiencing losses due to the many clients who fail to pay, this is due to several reasons from the PKL. Based on the Collectibility recapitulation report as of June 2017, BMT NU Temayang had a total of 274 customers, which was jammed by 5.57% and its NPF was 21.18%. While the Bank is said to be healthy if the NPF not more than 7%, it means that BMT NU Temayang has very serious problems related to the problem financing, because the number of NPF more than 7%. In the problem of financing there are institutions that function to deal with the issue is the BASYARNAS. The purpose of this research is to know how BMT NU Temayang's efforts in tackling the failed pay perspective of BASYARNAS. This research is a evaluative study with a qualitative approach. Its analytical techniques use interviews, documentation, and observations. The results of this study showed that the financing of Akad Rahn was given to the PKL as an initial business capital, an effort to overcome the financing of the Rahn contract conducted at BMT NU Temayang using the 5C strategy, family principle, Spiritual, and taking action Over collateral. While Basyarnas uses the way of peace, finishing with the principle (Ishlah), resolving disputes using Islamic law, resolve the dispute by making Islamic Sharia as a base. This makes BMT NU Temayang and BASYARNAS have a common in tackling the failing to pay that is by means of peace or family principle that provides humanist concept.